Manual Deskterity: An Exploration of Simultaneous Pen + Touch Direct Input - Hinckley, Ken; Yatani, Koji; Pahud, Michel; Coddington, Nicole; Rodenhouse, Jenny; Wilson, Andy; Benko, Hrvoje; Buxton, Bill (CHI EA '10 CHI '10 Extended Abstracts on Human Factors in Computing Systems, 2010)
Manual Deskterity is a prototype digital drafting table that supports both pen and touch input. We explore a division of labor between pen and touch that flows from natural human skill and differentiation of roles of the hands. We also explore the simultaneous use of pen and touch to support novel compound gestures.